Taxonomy for Credentialing Australasian University Educators (TCAUE) - Dinan-Thompson, Maree; Lynch, Andrea; Cowden, Gillian; Bedford, Simon; Branigan, Liz; Cary, Lisa; Johnston, Shannon; Luzeckyj, Ann; Saliba, Gina (James Cook University, 2022)
University educators make significant contributions to student success. The Taxonomy for Credentialing Australasian University Educators (TCAUE) recognises and values the role that educators have in student learning, and makes transparent the pathways for personal and professional development. As an Australasian credentialing framework, it is underpinned by regulatory requirements, is aligned to qualification and micro-credentialing frameworks, and permits university contextualisation and portability. The purpose of the TCAUE is to provide flexible, consistent, and portable educator professional development. The taxonomy is written from the standpoint that learning and teaching should be practice and evidence-based. It encompasses all educator roles, and learning and teaching contexts/communities. University educator roles include academic roles, part-time and sessional teaching, professional and technical positions, research supervision, clinical, laboratory, workshop, studio, field and work-based teaching, industry and advisory, and team-based contributions. In this sense, the taxonomy purposely uses the term ‘practices or context of practice' to be inclusive of all educator work and the taxonomy aligns well with the Universities Australia Statement of Principles for Professional Development and Recognition of Educators (Universities Australia, 2019). [Publisher summary, ed]